Supervision by Head Nurses in the Application of SBAR Communication in Nurse Handover Practices - Alpan Habibi; Enie Novieastari; Dewi Gayatri (CV Media Inti Teknologi, 2025)
Background of study: Supervision by head nurses in hospitals is often questioned regarding its optimal function. One key focus is the nurse handover using SBAR communication, which requires proper supervision to ensure its effectiveness.Aims and scope of paper: This study explores the experiences of head nurses in supervising SBAR communication during nurse handover activities.Methods: A qualitative design with a phenomenological approach was used. Data were collected through unstructured in-depth interviews with 14 head nurses, selected via purposive sampling based on inclusion and exclusion criteria. Data analysis was conducted using Colaizzi’s method and thematic analysis.Result: Seven main themes emerged: (1) Head Nurse Bank as a Supervision Solution during the Pandemic; (2) Conventional and Digital Supervision Cultures Across Eras; (3) Patient Safety as the Primary Reason for Supervision; (4) Collaboration in Supervision; (5) 4M Issues (Man, Method, Material, Machine); (6) Solutions to Challenges in SBAR Implementation; (7) Three Key Supporting Factors for Supervision.Conclusion: Head nurse supervision of SBAR communication during handovers is shaped by pandemic-related changes and requires a structured, collaborative, and technology-driven approach to enhance patient safety.